A conservative approach to adaptive call admission control for QoS provisioning in multimedia wireless networks - YEE, Y; CHOONG, K; LOW, A; TAN, S; CHIEN, S (ELSEVIER SCIENCE BV, 2007)
In this paper, we propose a framework called conservative and adaptive quality of service (CAQoS) to perform the quality of service (QoS) provisioning on both real-time and non real-time traffic in the wireless network. Unlike most conventional schemes which gradually scale-down the bandwidth rates of ongoing connections to accommodate new connection/handoff requests, CAQoS introduces an early scaling-down of bandwidth for new connections based on designated provisioning model. The objectives of CAQoS are to minimize the need for frequent bandwidth reallocation and to achieve lower call blocking and handoff dropping rates, while maximizing the overall bandwidth utilization. The performance of CAQoS system is evaluated through simulations of a realistic wireless cellular-based environment. Simulation results showed that CAQoS met our objectives and outperformed the conventional schemes. (c) 2006 Elsevier B.V. All rights reserved.